Bone turnover markers and vitamin D status over a training year in female elite alpine skiers - Lombardi, G.; Colombini, A.; Freschi, M.; Tavana, R.; Schonhuber, H.; Banfi, G. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: The training year of elite athletes is characterized by different kind and intensities of workload implying different level of metabolic responses of the skeletal tissue, assessable by measuring serum levels biochemical markers (Guadalupe-Grau et al., 2009).